2019
DOI: 10.1002/pri.1777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inspiratory muscle training on respiratory muscle strength, lung function, functional capacity and cardiac autonomic function in Parkinson's disease: Randomized controlled clinical trial protocol

Abstract: Background Individuals with Parkinson's disease (PD), in addition to motor impairment, may evolve with respiratory and autonomic nervous system disorders. Currently, there are few studies with emphasis on muscle and pulmonary dysfunction and that verify the benefits of inspiratory muscle training (IMT) in this population. Aim The aim of this study was to evaluate whether IMT is effective for the improvement of respiratory muscle strength, lung function, thoracic mobility, functional capacity and cardiac autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Pre-post intervention studies (that had been excluded from the analyses) showed similar positive effects for either strength training (EMST and IMST) and other respiratory training techniques like air stacking, or deep breathing exercises (plus upper extremity exercises) and (global) postural training to improve respiratory function tests, swallowing safety and phonatory aspects. [24,[26][27][28][31][32][33][34][35][36][37] This confirms that the positive results are robust, but also indicates that more high-quality studies for both respiratory strength training and volume-oriented training techniques remain needed. The included studies all showed positive effects, but the magnitude of the effects was different.…”
Section: Discussionmentioning
confidence: 68%
“…Pre-post intervention studies (that had been excluded from the analyses) showed similar positive effects for either strength training (EMST and IMST) and other respiratory training techniques like air stacking, or deep breathing exercises (plus upper extremity exercises) and (global) postural training to improve respiratory function tests, swallowing safety and phonatory aspects. [24,[26][27][28][31][32][33][34][35][36][37] This confirms that the positive results are robust, but also indicates that more high-quality studies for both respiratory strength training and volume-oriented training techniques remain needed. The included studies all showed positive effects, but the magnitude of the effects was different.…”
Section: Discussionmentioning
confidence: 68%
“…A randomized controlled trial in individuals with mild to moderate Parkinson disease suggested that increases in inspiratory muscle strength contribute to improved expiratory muscle strength, thoracic mobility, and functional capacity (Montero Ferro et al, 2019). As mentioned, it is likely that respiratory muscle strength is directly associated with chest wall expansion (Jung and Kim, 2018) and the latter directly correlates with lung volume (Ray et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers have concentrated on the simultaneous effects of RMST on lung and cardiovascular autonomic nervous function. Alyne Montero Ferro designed the study protocol to investigate the impact of IMST on the cardiac autonomic nerve and pulmonary function in 26 PD patients (modified Hoehn Yahr scale, Stage I ~ III) (Montero Ferro et al, 2019 ). Huang et al recruited 75 individuals with PD.…”
Section: Applications Of Respiratory Muscle Strength Trainingmentioning
confidence: 99%
“…Respiratory muscle strength training (RMST) can improve respiratory muscle strength and may prevent aspiration pneumonia (Troche et al, 2010 ; Kuo et al, 2017 ; Claus et al, 2021 ). Emerging applications using RMST, such as speech rehabilitation, have also been proposed (Montero Ferro et al, 2019 ; Huang et al, 2020a , 2021 ; Reyes et al, 2020a , b ; Cocks et al, 2022 ). 2014 European Physiotherapy Guideline for PD rehabilitation suggested that RMST can improve respiratory-related disorders of PD (Keus et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%